2022
DOI: 10.1186/s13765-022-00681-2
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation patterns of acrinathrin and metaflumizone in Aster scaber

Abstract: The establishment of preharvest residue limits (PHRLs) is important to minimize damage to producer and consumers caused by agricultural products which pesticide residue exceeds maximum residue limits (MRLs). Dissipation patterns of acrinathrin and metaflumizone in Aster scaber in greenhouse were studied during 10 days in order to determine a pre-harvest interval after application. Acrinathrin and metaflumizone were applied in two different greenhouse, located in Taean-gun (field 1) and Gwangyang-si (field 2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The dissipation proportions of CAP and FBD over 10 days were 60–68 % and 53–64 %, respectively. Similarly, the dissipation proportions of acrinathrin and metaflumizone in A. scaber were reported to be 56–83 % [ 24 ]. According to the GAP guidelines, the recommended PHI is 7 days for both CAP and FBD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The dissipation proportions of CAP and FBD over 10 days were 60–68 % and 53–64 %, respectively. Similarly, the dissipation proportions of acrinathrin and metaflumizone in A. scaber were reported to be 56–83 % [ 24 ]. According to the GAP guidelines, the recommended PHI is 7 days for both CAP and FBD.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the slower dissipation of pesticide residues in A. scaber than in other crops may be attributed to its lower enzymatic degradation capacity, resulting in prolonged persistence. Previous research has reported longer half-lives in A. scaber , such as 3.8–9.2, 4.5–5.9, 8.5, 5.8, and 7.6 days for acrinathrin, metaflumizone, methoxyfenzide, novaluron, and pymetrozine, respectively, which were determined by excluding any potential dilution effect [ 24 , 36 , 37 ]. These results are consistent with those of the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations